Project-Based Learning Model: A Strategy to Improved Reading Comprehension - Ayu Rizkilla; Aminah Suriaman; Andi Patmasari; Mochtar Marhum (Institut Agama Islam Negeri Palopo, 2025)
There are several problems in reading comprehension faced by students at SMP Negeri 14 Palu. The main issue is that when students read, they still have difficulty understanding the text due to limited vocabulary. Additionally, they also have difficulty with complex text structures and have a low interest in reading. Therefore, this research aims to prove that the Project-Based Learning method can improve reading comprehension of students in grade VIII of SMP Negeri 14 Palu. Researchers answer the problems above using a quasi-experimental research design, with cluster random sampling to select samples. There are 22 students in class VIII Slamet Triyadi and 22 students in class VIII Imam Bonjol. To collect data, researchers use narrative tests with 20 multiple-choice questions and 5 essay questions. In the essay section, students are required to create short narrative texts based on story elements. Based on the results of the research, it can be concluded that the use of the Project-Based Learning method is effective in improving the reading comprehension of grade VIII students at SMP Negeri 14 Palu. These findings can help teachers to get new methods designed to make students to think creatively. Through the project, students can delve deeper into the text, understand the context, and connect information with the real world.